2008
DOI: 10.1016/j.jacc.2008.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diabetes on Progression of Coronary Atherosclerosis and Arterial Remodeling

Abstract: Diabetes is accompanied by more extensive atherosclerosis and inadequate compensatory remodeling. Accelerated plaque progression, despite use of medical therapies, supports the need to develop new antiatherosclerotic strategies in diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
185
4
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 313 publications
(209 citation statements)
references
References 42 publications
12
185
4
8
Order By: Relevance
“…Furthermore, intravascular ultrasound findings also showed that the presence of diabetes was associated with a greater atherosclerotic burden and impaired compensatory remodeling of the artery wall. 36 In this study, a higher baPWV was significantly associated with an increasing number of diseased vessels in both CAD patients and CAD patients with diabetes, suggesting that baPWV may reflect the severity of CAD in the diabetic population. Although the duration and extent of diabetes appear to influence atherosclerosis levels and the prognosis in diabetic CAD patients, this study revealed that the baPWV, an index of arterial stiffness, can predict the prognosis in this population.…”
Section: Coronary Atherosclerosis and Diabetessupporting
confidence: 51%
See 1 more Smart Citation
“…Furthermore, intravascular ultrasound findings also showed that the presence of diabetes was associated with a greater atherosclerotic burden and impaired compensatory remodeling of the artery wall. 36 In this study, a higher baPWV was significantly associated with an increasing number of diseased vessels in both CAD patients and CAD patients with diabetes, suggesting that baPWV may reflect the severity of CAD in the diabetic population. Although the duration and extent of diabetes appear to influence atherosclerosis levels and the prognosis in diabetic CAD patients, this study revealed that the baPWV, an index of arterial stiffness, can predict the prognosis in this population.…”
Section: Coronary Atherosclerosis and Diabetessupporting
confidence: 51%
“…Intensive statin treatment may regress coronary atherosclerosis, but might not be effective in patients with diabetes. 36,39,40 There is an ongoing need to develop additional therapies with the aim of reducing the atherosclerotic burden and inhibiting cardiovascular events in CAD patients with both diabetes and advanced arterial stiffness.…”
Section: Cad and Diabetesmentioning
confidence: 99%
“…Moreover, poorly controlled DM is associated with a greater lipid burden 18. Intravascular ultrasound studies have shown that patients with DM and ACS have greater plaque burden and necrotic core volume at the culprit lesions compared with patients with ACS but not DM 20, 21. In contrast, previous OCT studies did not demonstrate the differences in the prevalence of lipid‐rich plaque or TCFA at the culprit lesion 6, 8, 22, 23.…”
Section: Discussionmentioning
confidence: 95%
“…154 Intensive lowering of LDL-C had a beneficial effect on progression of atheroma in DM and non-DM subjects. 155 Intensification of LDL-C lowering can be achieved by adding ezetimibe to a statin. Although there are no RCT data on CVD outcome, a trial is under way (IMPROVE-IT [IMProved Reduction of Outcomes: Vytorin Efficacy International Trial]: ClinicalTrials.gov: NCT00202878).…”
Section: Management Of Dyslipidaemiamentioning
confidence: 99%